1998
DOI: 10.1037/0022-3514.75.4.953
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in perceived controllability of mate value: An evolutionary perspective.

Abstract: Men and women value different characteristics in potential partners. It was hypothesized that women feel they have less control over traits relevant to their desirability than men feel they have over traits related to male desirability. In Study 1, undergraduates (N = 150) completed questionnaires measuring (a) the importance they attributed to 64 characteristics when choosing a mate and (b) their perceived control over these traits. Men selected partners on the basis of traits that are relatively uncontrollab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 89 publications
0
34
2
Order By: Relevance
“…Self-esteem should not just respond to capacity rejection in a mating relationship in general, but more specifically to one's being capacity rejected on the traits that contribute most to mate value. Men's desirability as a mate (compared with women's) seems more strongly dependent on traits associated with competence and social status whereas women's desirability (compared with men's) seems more strongly dependent on traits associated with physical attractiveness (e.g., Ben Hamida, Mineka, & Bailey, 1998;Buss & Schmitt, 1993;Li, Bailey, Kenrick, & Linsenmeier, 2002). Thus, young men and women may be especially sensitive not only to capacity rejection within mating relationships (compared to friendship relationships) but also to whether the rejection experience targets their most important trait as a mate.…”
mentioning
confidence: 99%
“…Self-esteem should not just respond to capacity rejection in a mating relationship in general, but more specifically to one's being capacity rejected on the traits that contribute most to mate value. Men's desirability as a mate (compared with women's) seems more strongly dependent on traits associated with competence and social status whereas women's desirability (compared with men's) seems more strongly dependent on traits associated with physical attractiveness (e.g., Ben Hamida, Mineka, & Bailey, 1998;Buss & Schmitt, 1993;Li, Bailey, Kenrick, & Linsenmeier, 2002). Thus, young men and women may be especially sensitive not only to capacity rejection within mating relationships (compared to friendship relationships) but also to whether the rejection experience targets their most important trait as a mate.…”
mentioning
confidence: 99%
“…Past research on effort supports the higher desirability ratings of the hardworking target (Ben Hamida et al, 1998;Bochner & Van Zyl, 1985). Hard work and industriousness, traits related to effort, are desirable traits for close others to possess.…”
Section: Abilitymentioning
confidence: 93%
“…Research shows that hard work and effort are desired characteristics for a person to possess and are a crucial and beneficial component of a relationship (Ben Hamida et al, 1998;Bochner & Van Zyl, 1985;Van Lange et al, 1997;Wieselquist et al, 1999). We also know that one specific trait can have a broad effect on how people perceive others.…”
Section: The Present Studymentioning
confidence: 99%
“…Alternatively, there are numerous studies have found that men compared to women place greater emphasis on a potential mate's availability for sexual relations (e.g., Regan et al 2008), youthfulness (e.g., Marlowe 2004;Hudson and Henze 1969;Hamida et al 1998), and physical beauty (e.g., Buss 1985Buss , 1994Buss et al 2001).…”
Section: Gender Differences In Mate Preferencesmentioning
confidence: 99%
“…Numerous studies have found that women compared to men prefer mates who are rich in resources (e.g., Buss 1985;Buss et al 1990;Fisman, Iyengar, Kamenica, and Simonson 2006;Goetz 2013;Gottschall, Martin, Quish, and Rea 2004;Iredale, Vugt, and Dunbar 2008;Hudson and Henze 1969;Asendorpf, Penke, and Back 2011;Buss, Shackelford, Kirkpatrick, and Larsen 2001), interested in commitment (e.g., Marlowe 2004;Hamida, Mineka, and Bailey 1998), and interested in child rearing (e.g., Hudson and Henze 1969;Hoyt and Hudson 1981;Buss et al 2001). Alternatively, there are numerous studies have found that men compared to women place greater emphasis on a potential mate's availability for sexual relations (e.g., Regan et al 2008), youthfulness (e.g., Marlowe 2004;Hudson and Henze 1969;Hamida et al 1998), and physical beauty (e.g., Buss 1985Buss , 1994Buss et al 2001).…”
Section: Gender Differences In Mate Preferencesmentioning
confidence: 99%